Correction: The Terezita Romo Papers: Capturing the Spirit of Collective Action in Archives - Ulinskas, Moriah (KULA)

(untitled) (University of Victoria Libraries, 2019)
This article details corrections to the article: Ulinskas, M., 2018. The Terezita Romo Papers: Capturing the Spirit of Collective Action in Archives. KULA: knowledge creation, dissemination, and preservation studies, 2(1), p. 4. DOI: http://doi.org/10.5334/kula.22